94 Secondary outcomes of spinal surgery in patients with spinal muscular atrophy (SMA): a retrospective analysis and a family-centred survey. (22nd November 2019) - Brusa, Chiara; Graaf, Julie De; Manzur, Adnan; Main, Marion; Milev, Evelin; Iodice, Mario; Ramsey, Danielle; Tucker, Stewart; Ember, Tom; Nadarajah, Ramesh; Muntoni, Francesco; Scoto, Mariacristina
Abstract : Background: SMA is a severe neuromuscular disorder characterised by progressive muscle atrophy, weakness, paralysis. Scoliosis is a highly prevalent feature and surgery is almost invariably required in 'sitters'. However, data are limited on post-surgical secondary outcomes (respiratory, motor function, weight gain, skeletal pain, satisfaction). Methods: 1. We retrospectively reviewed the notes of 33 patients who never walked/lost the ability to walk (SMA type II/III) and underwent spinal fusion (25), magnetic (4) or traditional (4) growth rods at Great Ormond Street Hospital; 2. We developed a phone interview and run a focus group for families on post-surgical satisfaction. Results: The curve was successfully corrected in all patients. Median follow-up before and after surgery was 3.9 (0.9–12.3) and 3.7 (0.4–10.5) years respectively. Mean annual rate of Forced Vital Capacity% decline improved after surgery in SMA II: -2.8 versus -7.4 (p<0.001); similar trajectories were observed in SMA III. At first post-surgery assessment a median decline of 4.5 points (0-14) was observed on the Hammersmith Functional Motor Scale; the Revised Upper Limb Module's scores showed a less progressive deterioration. A temporary negative deviation from previous weight curve was observed in 17/33 requiring food supplements (5); one/4 with significant weight loss (>5% of total weight) needed gastrostomy. Skeletal pain was frequently documented, especially hip pain (13/33) requiring painkillers (8), intra-articular steroids (1), surgical intervention (1). Nine/10 families participating in the phone interview reported major improvements in posture, physical appearance, self-image; all rated the procedure as very successful. However, 7/10 did not report significant improvements in quality of life due to reduced mobility and increased unmet care needs. Five families attended the focus group highlighting positive and negative aspects of their experiences. Conclusion: This study provided relevant data and suggestions to improve the current post-operative multidisciplinary approach of scoliosis surgery in children with SMA.